THE EFFECT OF PROMOTIONS, BRAND IMAGE, AND SERVICE FEATURES ON THE DECISION TO USE THE LINKAJA SHARIA E-WALLET IN THE CITY OF MALANG - Ririn Diyah Puspita; Rini Safitri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
This study aims to analyze the effect of promotion, brand image, and service features on the decision to use the LinkAja Sharia e-wallet in Malang City. The rapid development of financial technology and intense competition among e-wallet providers highlight the importance of understanding the factors influencing usage decisions, particularly for sharia-based services with relatively lower adoption rates. This research employs a quantitative approach using questionnaire data collected from 100 respondents. The sampling technique used is non-probability sampling with the purposive sampling method. Data analysis was conducted using IMB SPSS 23 software, including validity, reliability, classical assumption tests, and multiple linear regression analysis. The results indicate that promotion, brand image, and service features each have a positive and significant effect on usage decisions. Simultaneously, all variables significantly influence the decision to use the LinkAja Sharia e-wallet.